« I am the Resurrection and the Life » : Sydney Carton, ou les modalités du retour d’une figure familière dans A Tale of Two Cities - Isabelle Hervouet-Farrar (Cahiers Victoriens et Edouardiens)
Dickens’s preface to A Tale of Two Cities may lead his readers to consider the character of Richard Wardour (in Collins’s play The Frozen Deep) as the original model for Sydney Carton. Yet Sydney Carton appears as an altogether different type of hero, a falsely passive and indolent one. His ambiguous characterization shows a constant combination of the motifs of exclusion from and integration within a group, both at the diegetic and narrative levels. Sydney Carton’s oxymoronic characterization is never satisfactorily explained to the reader, and an analysis of the part he plays as Charles Darnay’s double simply emphasizes the motif of exclusion. An inter-textual reading of Dickens’s last novels tends to show that the double hero of A Tale of Two Cities marks the return of a familiar Dickensian figure : that of the man who is deprived of self-esteem and feels the constant urge to express the very poor opinion he has of himself, whilst at the same time finding modes of expression for something akin to passionate self-love. In that, Sydney Carton reminds one of Arthur Clennam (Little Dorrit), and announces the advent of later characters such as Pip (Great Expectations) and Eugene Wrayburn (Our Mutual Friend).